Firm surveys relating environmental policies, environmental performance and innovation: design challenges and insights from empirical application - Mazzanti, Massimiliano; Antonioli, Davide; Ghisetti, Claudia; Nicolli, Francesco (Paris, 2016)
"This report provides a review of recent firm-level and plant-level surveys containing questions on environmental policies, innovation practices or performance which are relevant for environmental policy analysis and assessment. We specifically focus on the core element that relates environmental policies to environmental and economic performance, namely the adoption of innovative practices and environmental innovations by firms. The study gives an overview of the main literature exploiting surveys, with the aim of discussing main themes and their core limitations to propose advancements for future research. The report provides technical details on surveyed questionnaire implementation, by focusing on to the intrinsic trade-off in the design of alternative questions. It also discusses how environmental policy and its stringency have been measured in previous literature. Finally, it provides suggestions on how to implement a multi-country survey and on other ways to better harness firm-level data in the analysis of effects of environmental policies on business behaviour."